Sinonasal synovial sarcoma: evaluation of the role of radiological and clinicopathological features in diagnosis. Issue 1 (January 2021) - Lin, N.; Liu, X.; Zhang, F.; Pan, Y.; Qi, M.; Sha, Y.
Abstract : AIM: To explore the value of radiological and clinicopathological features in the diagnosis of sinonasal synovial sarcomas (SS). MATERIALS AND METHODS: Six patients with sinonasal SS were studied retrospectively using computed tomography (CT; n= 6) and magnetic resonance imaging (MRI; n= 4). The radiological and clinicopathological findings in this series were reviewed. RESULTS: Three lesions were located, in both the nasal cavity, and the paranasal sinuses; one was located in the nasal cavity and nasopharynx, and the remaining two were located restrictively within the nasal cavity. An aggressive nature (invasion of adjacent structure) was found in four cases. At CT, lesions were found with isodensity with calcification mainly in the peripheral areas. Bony changes were visible in all cases. Five cases showed marked heterogeneous enhancement, and three cases contained necrotic or cystic areas. At MRI, haemorrhage was observed in three cases. All cases demonstrated the "triple sign", and two high-grade SS showed a "cobblestone-like" appearance on T2-weighted imaging (WI). All time–signal intensity curves (TICs) were of the washout type. The mean apparent diffusion coefficient (ADC) values of the two high-grade cases were lower than those of the low-grade or intermediate-grade cases. Histopathologically, all but one was of the monophasic type. During the 8–40 month period of follow-up, recurrence occurred in four cases. CONCLUSIONS: A sinonasal tumour exhibiting characteristic calcification and bony change, together with haemorrhage, "triple sign" or "cobblestone-like" appearance, should engender a diagnosis of SS. Highlights: Primary sinonasal synovial sarcoma is extremely rare. Radiologic features facilitate early diagnosis and treatment planning. T2-weighted imaging inhomogeneity should invoke the diagnosis.